Analisis Yuridis Pelindungan Korban Kekerasan Berbasis Gender Menggunakan Media Online di Indonesia - I Made Ridho Ramadhan; Hanuring ayu; Hafid zakariya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the legal protection of victims of Online Gender-Based Violence (OGBV) in Indonesia through harmonization of relevant laws and evaluate the implementation effectiveness. This research employs juridical-normative approach with descriptive-analytical and prescriptive methods. Data collected through library research on primary, secondary, and tertiary legal materials, analyzed qualitatively-normatively using legal hermeneutics approach. Research findings reveal fundamental structural disharmony in OGBV victim protection legal framework. The Sexual Violence Criminal Act Law adopts victim-centered approach but limited in digital dimensions, Electronic Information and Transactions Law implements law and order approach with minimal victim protection, while Pornography Law uses moral regulatory approach potentially criminalizing victims. Implementation faces systemic challenges including institutional unpreparedness, low conviction rates (34%), and high victim stigmatization (73%). Research concludes the need for systemic transformation through regulatory harmonization, National OGBV Task Force establishment, National OGBV Response System development, and institutional capacity strengthening.